Impact of a common genetic variation associated with putamen volume on neural mechanisms of attention-deficit/hyperactivity disorder - Xu, Bing; Banaschewski, Tobias; Flor, Herta; Poustka, Luise (Journal of the American Academy of Child and Adolescent Psychiatry, 2017)
Objective: In a recent genomewide association study of subcortical brain volumes, a common genetic variation at rs945270 was identified as having the strongest effect on putamen volume, a brain measurement linked to familial risk for attention-deficit/hyperactivity disorder (ADHD). To determine whether rs945270 might be a genetic determinant of ADHD, its effects on ADHD-related symptoms and neural mechanisms of ADHD, such as response inhibition and reward sensitivity, were explored. Method: A large population sample of 1,834 14-year-old adolescents was used to test the effects of rs945270 on ADHD symptoms assessed through the Strengths and Difficulties Questionnaire and region-of-interest analyses of putamen activation by functional magnetic resonance imaging using the stop signal and monetary incentive delay tasks, assessing response inhibition and reward sensitivity, respectively. Results: There was a significant link between rs945270 and ADHD symptom scores, with the C allele associated with lower symptom scores, most notably hyperactivity. In addition, there were sex-specific effects of this variant on the brain. In boys, the C allele was associated with lower putamen activity during successful response inhibition, a brain response that was not associated with ADHD symptoms. In girls, putamen activation during reward anticipation increased with the number of C alleles, most significantly in the right putamen. Remarkably, right putamen activation during reward anticipation tended to negatively correlate with ADHD symptoms. Conclusion: These results indicate that rs945270 might contribute to the genetic risk of ADHD partly through its effects on hyperactivity and reward processing in girls.